1970
DOI: 10.1111/j.1365-2494.1970.tb01094.x
|View full text |Cite
|
Sign up to set email alerts
|

The Position in the Plant and the Date of Origin of Tillers Which Produce Inflorescences

Abstract: The dates of their first appearance and the dates of flowering were recorded monthly over three years from time of sowing for all tillers produced by S21S meadow fescue plants growing in simulated sward conditions in large concrete pots outdoors. The results are expressed and discussed in terms of the percentage contribution of inflorescences by tillers in relation to their chronological and ontogenetic age. The latter appeared the more important. The major contribution of inflorescences was made by primary ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Any such consideration must take account of two factors, namely, the sequential origin of the tillers comprising the sward, and vernalization effects. Lambert & Jewiss (1970) found that the majority of the tillers contributing to seed crops of S. 215 meadow fescue arose during the summer/autumn of the preceding season; for tillers of a given order (primary . .…”
Section: Discussionmentioning
confidence: 99%
“…Any such consideration must take account of two factors, namely, the sequential origin of the tillers comprising the sward, and vernalization effects. Lambert & Jewiss (1970) found that the majority of the tillers contributing to seed crops of S. 215 meadow fescue arose during the summer/autumn of the preceding season; for tillers of a given order (primary . .…”
Section: Discussionmentioning
confidence: 99%
“…The high contribution of early forming tillers (following harvest in fall) to inflorescence population is supported by the findings of other workers with perennial ryegrass and Kentucky bluegrass (Saxby, 1956); timothy (Langer, 1956;Wilson, 1959), smooth bromegrass (Bromus inermis Leyss.) (Lamp, 1952), and orchardgrass (Dactylis glomerata L.) (Lambert, 1963;Lambert and Jewiss, 1970;Langer and Lambert, 1959). The major effect of applied N was to increase floret number per inflorescence (Hill and Watkin, 1975).…”
mentioning
confidence: 99%
“…This response is believed to have been due to the Tiller 2 daughter tillers having being initiated earlier than those of Tiller 5 and so were better developed suggesting that tiller age, perhaps through its relationship with tiller developmental stage, influences reproductive tiller initiation. Lambert & Jewiss (1970) stated that the young, less developed tillers provide the basis for the reproductive tiller population only in the year following their initiation. Furthermore, Lambert & Jewiss (1970) and Colvill & Marshall (1984) observed that in both Festuca pratensis and Lolium perenne the main components of the flowering tiller population in the first year was formed by the main shoots and primary tillers, by the secondary and tertiary tillers in the second year, by tertiary and quaternary tillers in the third year and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Although many tillers are produced by a pasture, only a small proportion of these become reproductive (Langer 1959;Lambert 1968;Lambert & Jewiss 1970). The number which become reproductive and the seed production from each is influenced by many management factors, for example plant density, nitrogen (N) fertilization, cutting and position of tillers on the plant (Lambert 1963(Lambert , 1968Lambert & Jewiss 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation